Engaging College Students by Singing the Science - Richard H. Heineman (American Society for Microbiology, 2017)
Setting scientific ideas to music can increase student engagement and help with memorization. However, some instructors may be intimidated by the thought of performing educational music for their STEM students, or concerned that it is frivolous. To address this issue, I spell out step by step protocols for either writing one’s own parody songs to teach specific concepts, or finding songs online (which can be used directly or modified). I also discuss presentation techniques that help students, such as showing lyrics and adding annotations that clarify or emphasize ideas. A survey suggests that this approach is appreciated and effective.